2005
DOI: 10.1124/jpet.105.085522
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Atorvastatin on Apolipoprotein E and AI Kinetics in Patients with Type 2 Diabetes

Abstract: Atorvastatin reduces both plasma cholesterol and triglyceride concentrations in patients with type 2 diabetes, but mechanisms underlying triglyceride decrease and the effect of atorvastatin on high density lipoprotein (HDL) still remain unclear. Apolipoprotein (apo) E plays a crucial role in modulating production and clearance of triglyceride-rich very low density lipoprotein (VLDL). The main effect of apoAI is to modulate HDL metabolism. The aim of this work was to study the influence of atorvastatin on apoAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 39 publications
7
22
0
Order By: Relevance
“…In our study, no significant effect of atorvastatin on apoA-I PR or FCR was observed. These results are in agreement with previously published studies indicating no effect of atorvastatin on the kinetics of apoA-I (6,(40)(41)(42)(43). The change in HDL-C with atorvastatin was independent of apoA-I kinetics.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, no significant effect of atorvastatin on apoA-I PR or FCR was observed. These results are in agreement with previously published studies indicating no effect of atorvastatin on the kinetics of apoA-I (6,(40)(41)(42)(43). The change in HDL-C with atorvastatin was independent of apoA-I kinetics.…”
Section: Discussionsupporting
confidence: 93%
“…Higher VLDL apoE concentration and PR were associated with elevated plasma and VLDL triglycerides ( 25,27 ). Our subjects exhibited overproduction of VLDL apoE, with concentrations of plasma and VLDL apoE within range of those previously reported in hypertriglyceridemic subjects ( 20,21,25,27 ). It is, however, important to acknowledge that, in this study, VLDL apoE PR represents the transport of apoE through the VLDL pool.…”
Section: Data Interpretationsupporting
confidence: 58%
“…The kinetics of HDL apoE were not examined in our subjects. Previous studies suggest that atorvastatin altered apoE distribution between VLDL and HDL in type 2 diabetic subjects ( 20 ). Therefore, the reported increase in VLDL apoE FCR with fenofi brate and atorvastatin may represent increased removal of VLDL apoE into tissues or organs, with or without the whole VLDL particle, or a greater fraction of VLDL apoE that is transported to HDL per unit time.…”
Section: Previous Kinetic Studiesmentioning
confidence: 85%
See 2 more Smart Citations